StaBle Angina: PeRceptIon of NeeDs, Quality of Life and ManaGemEnt of Patients (BRIDGE Study)—A Multinational European Physician Survey. (May 2019) - Ambrosio, Giuseppe; Collins, Peter; Dechend, Ralf; Lopez-Sendon, Jose; Manolis, Athanasios J.; Camm, A. John
Stable angina (SA) is a chronic condition reducing physical activity and quality of life (QoL). Physicians treating patients with SA in Italy, Germany, Spain, and United Kingdom completed a web-based survey. The objective was to assess physician perceptions of patient needs, the impact of SA on QoL, and evaluate SA management. Overall, 659 physicians (cardiologists and general practitioners) entered data from 1965 eligible patients. The perceived importance of everyday activities for patients with a recent diagnosis (≤2 years) was higher than for patients with a longer diagnosis (>2 years), while severity of limitations for those activities were rated similarly for both groups. Gender-based analyses revealed that physicians documented more severe SA, more symptoms and more angina attacks in women, yet they rated the patients' condition as similar for both sexes. Women also received less medical and interventional treatment. Patients who have previously had a percutaneous coronary intervention (PCI) had more severe SA, despite more intense medical treatment, than patients with no previous PCI. In conclusion, severity, symptoms, and impact of SA on health status and everyday life activities vary by duration of disease, gender, and previous PCI. However, physicians do not seem to attach appropriate importance to these differences.